The Influence of Human Resource Management on Employee Performance in the Digital Era - Riesnandar, Edi; Listiorini, Dewi; Feriandy, Feriandy (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rapid development of digital technology has significantly changed Human Resource Management (HRM) practices. This study aims to analyze the influence of digital HRM practices specifically digital recruitment, technology-based training, and information system supported performance management on employee performance in the digital era. This study uses a quantitative approach through a survey of 120 employees in the information technology services sector in Jakarta. Data analysis was carried out using multiple linear regression to determine the extent to which each digital HRM variable influences performance. The results of the study indicate that all three digital HRM practices have a positive and significant effect on employee performance. Digital recruitment accelerates the process of searching for and selecting more appropriate candidates. Technology-based training increases flexibility and learning effectiveness. Meanwhile, digital performance management allows for more transparent, accurate, and real-time evaluations. Overall, the three variables explain 67% of the variation in employee performance.